2020
DOI: 10.1371/journal.pone.0238942
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule real-time sequencing of the full-length transcriptome of loquat under low-temperature stress

Abstract: In this study, third-generation full-length (FL) transcriptome sequencing was performed of loquat using single-molecule real-time(SMRT) sequencing from the pooled cDNA of embryos of young loquat fruit under different low temperatures (three biological replicates for treatments of 1˚C,-1˚C, and-3˚C, for 12 h or 24 h) and the control group(three biological replicates for treatments of room temperature), Illumina sequencing was used to correct FL transcriptome sequences. A total of 3 PacBio Iso-Seq libraries (1-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The third-generation single-molecule real-time (SMRT) sequencing platform can capture full length transcripts and avoid the assembly process [30]. SMRT sequencing has been widely used in many plant species such as Arabidopsis pumila [31], rice [32,33], moso bamboo [34], loquat [35], orchid (Bletilla striata) [36], danshen (Salvia miltiorrhiza Bunge) [37] and sugarcane [38] which have provide thousands of high quality full length transcripts and facilitated the identification of alternative splicing. In this study, the upgraded PacBio SMRT Sequel platform was employed to generate a full length transcriptome of A. glabrata.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The third-generation single-molecule real-time (SMRT) sequencing platform can capture full length transcripts and avoid the assembly process [30]. SMRT sequencing has been widely used in many plant species such as Arabidopsis pumila [31], rice [32,33], moso bamboo [34], loquat [35], orchid (Bletilla striata) [36], danshen (Salvia miltiorrhiza Bunge) [37] and sugarcane [38] which have provide thousands of high quality full length transcripts and facilitated the identification of alternative splicing. In this study, the upgraded PacBio SMRT Sequel platform was employed to generate a full length transcriptome of A. glabrata.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Intriguingly, our previous studies have unveiled a bud sport mutant derived from the yellow-fleshed Dongting loquat, which displayed an alluring white flesh phenotype ( Sun et al., 2012 , 2017 ). This white-fleshed mutant, known as TBW, remarkably differs from the wild type (TBY) in terms of fructose content, flesh texture, maturity, and cold tolerance, highlighting its great potential for breeding purposes ( Sun et al., 2011 ; Li et al., 2016 ; Chen et al., 2017 ; Li et al., 2017 , 2020 ; Pan et al., 2020 ). Recent studies have shown that TBW has a 321-bp deletion in the PSY2A gene, which encodes a rate-limiting enzyme involved in carotenoid synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Loquat is native to the subtropical regions of humid heat, and its phylogeny is influenced by climatic environments, making it very sensitive to low temperatures [ 2 , 3 ]. The loquat differs from other fruit trees in that its phenological period is generally autumn–winter flowering and fruiting, so its flower and juvenile fruit development is highly susceptible to low-temperature stress, resulting in reduced yields [ 4 , 5 ]. With the recent increase in extreme weather, low temperatures have become one of the most common stressors in plants, with cold and frost damage greatly impacting plant growth and development [ 6 ].…”
Section: Introductionmentioning
confidence: 99%